Pengaruh Media Sosial Terhadap Perkembangan Anak Remaja - Alcianno G. Gani (JURNAL MITRA MANAJEMEN, 2015)
ABSTRACTDevelopment of Internet technology today is very rapid, as eliminating distance, spaceand time. We can connect with the world community wherever and whenever to find andshare information and ideas. With so many social networking we will be able to quicklyand easily establish networks and contacts. Besides, social media also brings a lot of newimpact in the development of our lives, especially in the development of children andadolescents, both negative and positive impacts.The users of social networking is mostly among children and adolescents who still needparental supervision in its use. Social media has a positive impact and advantages in thedevelopment of science and technology for example facilitate the communication, searchand access information, develop relationships, add friends and so forth, but on the otherhand social media also has negative impacts on the children and adolescents like changeof attitude shown after they are addicted to social networks such they become lazybecause too preoccupied with their social networks, they also forget their obligations asstudents.Keywords: Social Network, Social Media, Internet, adolescents